Surgical treatment of the lower leg open fracture with lesions of the main blood vessels. A case report - Stojiljković Predrag; Jovanović Milan; Golubović Ivan; Radovanović Zoran; Stevanović Goran; Golubović Ivana; Đorđević Dušan; Mitić Aleksandar; Milijić Svetlana; Golubović Zoran (Vojnosanitetski Pregled)
Introduction. Open fractures of the lower leg degree IIIC by Gustilo belong to the most serious open fractures of the lower leg segment.These fractures are, along with the main blood vessels damage, often followed by a severe soft-tissue damage of the lower leg. Case report. Patient 20 years old, sustained a severe open fracture of the left lower leg in a car accident, with the disruption of the continuity of the main left lower leg arteries. After clinical examination and radiography (X-ray) diagnosis, the primary treatment of the open fracture fragment wound, reposition of the left lower leg and stabilization of the open fractures by the external skeletal fixator were performed. In the postoperative period, there was a manifestation of acute ischemia of the left foot. Arteriography verified discontinuity of all three crural arteries at the level of the fracture line. The patient was immediately surgically treated. Revascularization of the extremities was performed by reconstruction of the anterior tibial artery by 15 centimeters long saphenous graft interposition with creation of distal anastomosis at the level of the dorsal artery of the foot. Large soft tissue defect and reconstructed vessels were covered with transpositional fasciocutaneous flap. The postoperative course was accompanied by proper graft flow. Control X-ray examination verified fracture of the distal pin of external skeletal fixator with the healing of fractures of the tibia with angular deformity. The external fixator was removed, except for the residual part of the pin in the distal part of the lower leg. During the control examination after completion of the treatment, the patient walked without mobility aid. Conclusion. External skeletal fracture fixation, damaged blood vessels reconstruction and early covering of the soft-tissue shin defect are basic elements in saving the injured limb. The long term goal of treatment of open lower leg fractures with an injury of the main blood vessels is to allow patients return to usual daily activities and professional work. [Projekat Ministarstva nauke Republike Srbije, br. III 41017: Virtual human osteoarticular system and its application in preclinical and clinical practice]